Lights on MsFLASH: a review of contributions. Issue 4 (April 2020) - Reed, Susan D.; LaCroix, Andrea Z.; Anderson, Garnet L.; Ensrud, Kristine E.; Caan, Bette; Carpenter, Janet S.; Cohen, Lee; Diem, Susan J.; Freeman, Ellen W.; Joffe, Hadine; Larson, Joseph C.; McCurry, Susan M.; et al.
Abstract: Objective: The Menopause Strategies: Finding Lasting Answers for Symptoms and Health clinical trials network was funded by the National Institutes of Health to find new ways to alleviate the most common, bothersome menopausal symptoms by designing and conducting multiple concurrent clinical intervention studies, accommodating a wide scope of populations and intervention strategies. Methods: Trials were conducted in Boston, Indianapolis, Minneapolis, Oakland, Philadelphia, and Seattle, with the Data Coordinating Center in Seattle, and were designed with standardized eligibility criteria and endpoints. Primary outcomes focused on vasomotor symptoms, sleep quality and insomnia symptoms, and vaginal symptoms. Secondary outcomes included quality of life, sexual function, and mood. Results: We completed five randomized clinical trials and three ancillary studies, testing nine interventions in over 1, 300 women and collecting nearly 16, 000 bio-specimens. Escitalopram, venlafaxine hydrochloride extended release, and low-dose estradiol diminished hot flashes by approximately 50% as compared with a 30% decrease by placebo. No benefits on vasomotor symptoms were observed with yoga or exercise compared with usual activity, nor with omega-3 supplementation compared with placebo. Cognitive behavioral therapy for insomnia reduced self-reported insomnia symptoms and improved overall sleep quality compared with menopause education control. We did not find significant benefit from a vaginal estradiol tablet or a vaginal moisturizer compared with placebo tablet and gel in diminishing the severity of vaginal symptoms. Conclusions: The MsFLASH trials contributed substantially to our understanding of bothersome menopausal symptom treatment. It is important that clinicians counseling women about available treatment options consider all therapies—both nonhormonal and hormonal. Abstract : Supplemental Digital Content is available in the text